The policy-making process in the Andean Community. A proposal based on four policy modes - Cárdenas Vargas, Diego Fernando (2025)
Latin American scholars, who have studied the Andean subregional integration process, viewed the Andean Community as a less effective attempt to follow the European Union model and pointed to its diffuse institutional framework and the divergent political vision of the Andean countries as deficiencies. However, European scholars, who have addressed their regional integration process, and even compared it with the Andean one, started from a different theoretical notion by cataloging them as supranational political systems, which allowed them, unlike the Latin American scholars, to introduce theoretical and methodological tools of Political Science to understand the policy-making process in the European Union.In this sense, the research article seeks to understand the policy-making process in the Andean Community, incorporating theories, approaches and methodologies of International Relations and Political Science to understand the particularity of Andean policies. In this sense, four modes of policy-making are proposed, categorized as “intergovernmental-political”, characterized by the role of the Andean Presidential Council in defining Andean subregional integration policy and in putting certain issues on the agenda; “intergovernmental-regulatory”, characterized by the guiding role that CAMRE and the Commission play in the design and adoption of policies; “intergovernmental-technical”, characterized by the role that the General Secretariat of the Andean Community plays in the design and adoption of policies; and “multilateral-autonomous”, characterized by the differentiated path taken by certain institutions of the Andean Integration System that develop their own policies with the participation of more Member Countries.